The hypoglycemic effect of aqueous extract of leaves of Smallanthus sonchifolius (yacon) in patients with Type 2 Diabetes Mellitus - Gordillo, Gloria c. (2012)
The present study was conducted to evaluate the hypoglycemic effect of Smallanthus sonchifolius (yacon) leaves, in the form of infusion (aqueous extract) administered to patients with type 2 diabetes mellitus. After signing informed consent, were included 206 people aged 30 to 70 years old, male and female: 105 diagnosed with type 2 diabetes mellitus and 101 apparently healthy control group. Type 2 diabetic patients were people who go to Scholar Healthcare of Clinical Analysis (SAAAC), Office of Pharmaceutical Care (GAF) of the Faculty of Pharmacy and Biochemistry, Club of type 2 diabetic patients of Cayetano Heredia Hospital and Patrucco Raul Puig Health Center (CERIT). From type 2 diabetic patients receiving drug treatment, there were 46 metabolically controlled patients and 59 not metabolically controlled ones. The latter group was given filter bags of yacon leaves of 1 g each, to be taken as an infusion three times a day for 90 days, plus glibenclamide. The apparently healthy subjects were divided into two groups, one ingested the yacon leaf tea and the other not. All were determined in fasting: glucose concentration, glycosylated hemoglobin (HbA1c) and fructosamine before and after treatment. After treatment, it was found that administration of the leaf tea yacon values decreased by 42.7 % glucose, glycosylated hemoglobin 21.7 % and fructosamine 33,78 %, with a statistically significant difference with baseline values. The effectiveness of the studied combination is able to reduce HbA1c by 4.5 % at 30 days and 21.7 % at 90 days. In conclusion, infusion of leaves Smallanthus sonchifolius (yacon) administered to patients with type 2 diabetes mellitus, has a beneficial protective effect on glycemic control.